지방 소재 대학 신입생 영어 말하기 능력과 한국어 말하기 능력 자기 인식 간의 관계 탐색 연구 - 이효신(Lee, Hyoshin) (영어학, 2024)
This study aims to assess the level of English-speaking proficiency in university foundational education aimed to enhance communication competence and to investigate self-perceptions of speaking in the native language, Korean, and then analyze the relationship between these two factors. It analyzed data collected online over three weeks from 1,182 first-year university students who enrolled in 2024. The data was gathered through a mock OPIc test, a standardized English speaking proficiency exam, and a self-perception survey on the students’ speaking abilities. To summarize the findings, the students who enrolled in 2024 at K Private University in a provincial area demonstrated a low level of English-speaking ability, classified as Novice on the OPIc scale, while their self-perception of Korean speaking competence was found to be at an intermediate level. The factors that showed differences in English speaking ability and self-perception of Korean speaking competence included the college affiliation, speaking learning experience, and leadership experience. Additionally, there was a statistically significant difference between English speaking ability and self-perception of Korean speaking competence. Factors contributing to these differences may include language proficiency, the quantity and quality of learning experiences, test design and evaluation criteria, and sociocultural factors. Based on these findings, suggestions for improving both English and Korean speaking education were provided. KCI Citation Count: 0